2013
DOI: 10.1002/bit.25112
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a pressure release on virus retention with the Ultipor DV20 membrane

Abstract: Recent data have shown that a temporary release in the transmembrane pressure can cause a significant increase in virus transmission through a number of commercial virus filters. The objective of this work was to study the effect of a pressure release on retention of the bacteriophage ΦX174 by the Ultipor DV20 membrane, with phage capture within the membrane visualized by confocal microscopy. Phage challenge tests showed a significant transient increase in phage transmission (typically by an order of magnitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 13 publications
4
33
0
Order By: Relevance
“…The results with the DV20 (Fig. a) are similar to those reported previously by Woods and Zydney (). There is a slight increase in phage concentration during the first portion of the experiment, with a 2‐log (100‐fold) increase in phage transmission immediately after the pressure release followed by a more gradual decline.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The results with the DV20 (Fig. a) are similar to those reported previously by Woods and Zydney (). There is a slight increase in phage concentration during the first portion of the experiment, with a 2‐log (100‐fold) increase in phage transmission immediately after the pressure release followed by a more gradual decline.…”
Section: Resultssupporting
confidence: 90%
“…There is a slight increase in phage concentration during the first portion of the experiment, with a 2‐log (100‐fold) increase in phage transmission immediately after the pressure release followed by a more gradual decline. Woods and Zydney () observed a much more rapid decline in phage concentration after the pressure release, with the permeate concentration returning to approximately the value obtained before the pressure release after about 9.5 L/m 2 . The filtrate flux during filtration of φX174 through the DV20 membrane (data not shown) remained nearly constant during the initial stage of the filtration at a value of 8.0 × 10 −6 m/s (30 L/m 2 /h) but increased by approximately 30% immediately after the pressure release and then remained constant.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…An industry‐wide evaluation of small virus retentive filters also found that large enveloped viruses were reduced below the limit of detection in all 198 cases examined, providing additional rationale that viral testing only needs to be performed with smaller virus as a worst case scenario . It has been shown that virus breakthrough can occur with small virus retentive filters during long processing times . However, proper evaluation and control of process parameters and solution properties can maintain high filter flux and mitigate this risk .…”
Section: Scientific and Technology Considerationsmentioning
confidence: 97%
“…Data for virus retentive filters have been summarized in a publication by Miesegaes et al [34]. Process operating ranges and depressurization have been reported to impact virus bleed through for virus-retentive filters designed to remove parvoviruses [35]. Sustained pressure excursions had a greater impact on log reduction values than the pressure differential (dP).…”
Section: Viral Filtrationmentioning
confidence: 98%